Exploring the Benefits and Challenges of Project-Based Learning in Higher Education - Evenddy, Sutrisno Sadji; Gailea, Nurhaeda; Syafrizal, Syafrizal (PPSDP International Journal of Education, 2023)
This study explores the benefits and challenges of Project-Based Learning (PjBL) in higher education. The research methodology employed a review study, utilizing various tools, methods, and software such as databases, citation management software, and data analysis software. The main findings of this study highlight the multifaceted benefits of PjBL in higher education, including enhanced student engagement, interdisciplinary collaboration, and authentic problem-solving. Implementing PjBL in higher education also presents challenges. These include faculty resistance and readiness, complexities in curriculum design and assessment, time and resource constraints, and the need for effective project management strategies. Strategies to address these challenges are discussed, including faculty training and support, curriculum alignment, assessment rubrics, and project management frameworks. This study’s findings can be useful in higher education institutions across various disciplines and areas, providing insights for educators, administrators, and policymakers who seek to integrate or enhance PjBL approaches in their curriculum. This study contributes to the existing knowledge on PBL in higher education by providing a comprehensive exploration of its benefits and challenges. It advances the understanding of how PjBL promotes active engagement, interdisciplinary collaboration, and authentic problem-solving, ultimately bridging the gap between theory and practice in education.